Development of high-throughput sample preparation procedures for the quantitative determination of aflatoxins in biological matrices of chickens and cattle using UHPLC-MS/MS - Baere, S. de; Ochieng, P.E.; Kemboi, D.C.; Scippo, M.-L.; Okoth, S.; Lindahl, Johanna F.; Gathumbi, J.K.; Antonissen, G.; Croubels, S. (MDPI, 2023)
Aflatoxins (AFs) frequently contaminate food and animal feeds, especially in (sub) tropical countries. If animals consume contaminated feeds, AFs (mainly aflatoxin B1 (AFB1), B2 (AFB2), G1 (AFG1), G2 (AFG2) and their major metabolites aflatoxin M1 (AFM1) and M2 (AFM2)) can be transferred to edible tissues and products, such as eggs, liver and muscle tissue and milk, which ultimately can reach the human food chain. Currently, the European Union has established a maximum level for AFM1 in milk (0.05 µg kg−1). Dietary adsorbents, such as bentonite clay, have been used to reduce AFs exposure in animal husbandry and carry over to edible tissues and products. To investigate the efficacy of adding bentonite clay to animal diets in reducing the concentration of AFB1, AFB2, AFG1, AFG2, and the metabolites AFM1 and AFM2 in animal-derived foods (chicken muscle and liver, eggs, and cattle milk), chicken and cattle plasma and cattle ruminal fluid, a sensitive and selective ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method has been developed. High-throughput sample preparation procedures were optimized, allowing the analysis of 96 samples per analytical batch and consisted of a liquid extraction using 1% formic acid in acetonitrile, followed by a further clean-up using QuEChERS (muscle tissue), QuEChERS in combination with Oasis® Ostro (liver tissue), Oasis® Ostro (egg, plasma), and Oasis® PRiME HLB (milk, ruminal fluid). The different procedures were validated in accordance with European guidelines. As a proof-of-concept, the final methods were used to successfully determine AFs concentrations in chicken and cattle samples collected during feeding trials for efficacy and safety evaluation of mycotoxin detoxifiers to protect against AFs as well as their carry-over to animal products.